(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study examined the impact of learning environment on students’ academic performance in Post-Basic Education and Career Development (PBECD), in FCT, Nigeria. The paper used secondary data. The secondary data were collected from both print and online publications. Content analysis was used to analyze the selection of literature for the study. The paper concluded that there is significant relationship between learning environment and students’ academic performance in Post-Basic Education and Career Development (PBECD) in FCT, Nigeria. Based on this the government should provide every human and materials resources that will make school environment conducive for learning. The private institutions should support secondary schools in Nigeria by provide infrastructure facilities and learning materials that will aid implementation of teaching and learning in schools.